114 Daily patterns of violence and associated substance use among a high-risk urban sample. (19th September 2017) - Carter, Patrick; Cranford, Jim; Buu, Anne; Walton, Maureen; Zimmerman, Marc; Dora-Laskey, Aaron; Cunningham, Rebecca
Abstract : Statement-of-Purpose: This analysis examined daily patterns of violence among emerging adults. Methods/Approach: Participants (n=352) from a 2 year study (Flint Youth Injury Study) of drug-using youth seeking ED care (for assault or other reasons) were enrolled in a 2nd wave study, in which they were randomised to complete daily or weekly assessments. This analysis examines daily data (n=162); 19-items measured violence (aggression/victimisation, partner/non-partner) and associated substance use, and were collected prospectively via either IVR (n=81) or text (n=81) over 90 days. Results: Participants [n=162; age=24.4; 62.3% African-American; 67% public assistance;59% ED visit for assault] completed an average of 48.3-daily reports [SD=26.9;range=1–89]. During the 90 day period, 27% of participants reported violence, with 65% reporting one violent day and 53% of violence days occurred on weekends. Among 118-violence days, 42% were with a partner (58% non-partner); 61% involved aggression (58%-victimisation); and 53% involved severe violence (e.g., beat-up, gun/knife). Among those involved with violence, 45% reported using drugs, alcohol, or both in the 3 hours before the encounter. Alcohol (OR=4.6, p<0.05) and marijuana (MJ;OR=4.0, p<0.05) use were independently associated with a higher odds of violence. Aggregating across 90 days, prevalence of substance use was: 78% alcohol; 75% MJ; 17% illicit drugs; 25% prescription opioid; 15% stimulant, and 19% sedative use. On average, participants reported 10 days of alcohol and 27 days of MJ use, with alcohol use highest on weekends; 34% of drinking days involved binge drinking, 5% concurrent opioid use. Conclusion: Among a high-risk sample, nearly a third of participants reported violent encounters during the 90 day period, with rates highest on weekends. Substance use preceded violent encounters on almost half of violence days, highlighting the relationships (e.g., acute pharmacological, clustering of problem behaviours) that exist between substance use and violence. Significance/Contribution: Prior studies characterising daily violence behaviours are limited and data will aid future intervention development for violence prevention initiatives.